Konsep Keruangan pada Permukiman Inti di Desa Pakraman Gunungsari - Cantika Putri, Gusti Ayu (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2017)
This article discusses the strategic plan for Gunungsari Village. As a desa wisata (village (community)-based tourism), the intention is to guide the industry while conserving the social, cultural, and spatial environments. It is based on a research study that employed qualitative method and naturalistic paradigm. Data collection was carried out through physical observations, interviews, and study to relevant literatures. Result of this study proposes the implementation of a community based economy by conserving the existence of Gunungsari agricultural land and the full engagement of its community members in the process. It is also underlined the need to isolate tourism related activities to a specific zone. This is to isolate damaging impacts of tourism on local resources. This strategy also anticipates a possibility in which the industry is participated by investors who inevitably come with less/no intention to protect local culture, social interactions, and space. This is a pivotal aspect of the strategic plan, since Gunungsari has been well-known for its natural beauties decorated by beautifully laid paddy fields and resourceful water springs everywhere. Keywords: desa wisata, strategic plan , economic development